2016
DOI: 10.1073/pnas.1609018113
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of visual pigments in vivo

Abstract: It is a deeply engrained notion that the visual pigment rhodopsin signals light as a monomer, even though many G protein-coupled receptors are now known to exist and function as dimers. Nonetheless, recent studies (albeit all in vitro) have suggested that rhodopsin and its chromophore-free apoprotein, R-opsin, may indeed exist as a homodimer in rod disk membranes. Given the overwhelmingly strong historical context, the crucial remaining question, therefore, is whether pigment dimerization truly exists naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Members of the opsin family, in particular, have been recently shown to form hetero-and homomeric complexes [39,40]. To determine whether OPN3 and MC1R colocalize to the same cellular compartments, we expressed tagged OPN3 and MC1R in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the opsin family, in particular, have been recently shown to form hetero-and homomeric complexes [39,40]. To determine whether OPN3 and MC1R colocalize to the same cellular compartments, we expressed tagged OPN3 and MC1R in HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…This raises the intriguing question of whether OPN3 functions in the brain similar to how it does in melanocytes: could OPN3 interact and negatively regulate the function of other melanocortin receptors like MC3R? OPN3 is not the only opsin that functions as part of a dimeric complex; a functional homomeric complex has also been reported for rhodopsin (OPN2) and cone opsin (OPN1) [40]. These complexes are mediated by residues within the fifth transmembrane domain of human red and green opsins [39], and by transmembrane domain one and helix eight for rhodopsin dimerization [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports indicate that GPCRs can form functional and physical interactions (37,38). Members of the opsin family, in particular, have recently been shown to form heteroand homomeric complexes (39,40). To determine whether OPN3 and MC1R colocalize to the same cellular compartments, we expressed epitope-tagged OPN3 and MC1R in HeLa cells.…”
Section: Mnt-1 Cells Transfected With Epacmentioning
confidence: 99%
“…A recent study of murine S-opsin reported cotrafficking with R-opsin, suggesting that it dimerizes with rhodopsin in a mouse model. 48 Another study noted blue cone opsin aggregation due to a Phe-rich region in this receptor, 49 but the aggregated protein was located in the ER and trans-Golgi network instead of the plasma membrane. Using the approach outlined above, we found that red cone opsin was significantly dimerized, and that the average cross-correlation was higher than that of rhodopsin.…”
mentioning
confidence: 97%